Tengdan Capsule Prevents Hypertensive Kidney Damage in SHR by Inhibiting Periostin-Mediated Renal Fibrosis - Du, Xiaoli; Tao, Qianqian; Du, Hongxia; Zhao, Zhenbang; Dong, Yu; He, Shuang; Shao, Rui; Wang, Yule; Han, Wenrun; Wang, Xintong; Zhu, Yan (Frontiers in Pharmacology, 2021)
BACKGROUND: Hypertension-induced renal damages are serious and complex, which have not been effectively treated by conventional blood pressure lowering drugs. Tengdan capsule (TDC) is a China FDA-approved compound herbal medicine for treating hypertension in the clinic. However, its chemical basis and pharmacological efficacy have not been fully investigated in a preclinical setting. RESULTS: Seven chemical compounds, namely Notoginsenoside R1, Ginsenoside RG1, Ginsenoside Re, Ginsenoside Rb1, Sodium Danshensu, Protocatechualdehyde and Salvianolic acid B, were identified and quantified from the water-soluble extracts of TDC by HPLC. In vivo rat studies showed that TDC effectively reduced BP, BUN and CRE levels and attenuated renal fibrosis in SHR, and reduced hypertension-induced damage to kidneys. Proteomics and subsequent bioinformatics analyses indicated that periostin-mediated inflammatory response and TGFβ/Smad signaling pathway proteins were closely related to the therapeutic effect of TDC in rat kidney. Results of western blot analysis and RT-qPCR showed that TDC markedly downregulated the mRNA and protein expression of periostin in renal tissues compared to the untreated SHR. In addition, TGF-β and COL1A1 mRNA levels also decreased in SHR renal tissues following TDC treatment. In vitro studies showed that low to medium doses of TDC down-regulated the expression of periostin in Angiotensin ǁ-induced HEK293 cell injury. In addition, medium to high doses of TDC significantly inhibited collagen deposition in TGFβ1-induced HEK293 cell fibrosis. CONCLUSIONS: Major components from compound herbal medicine Tengdan Capsule are identified and quantified. TDC effectively lowers blood pressure and protects hypertension-induced renal damage in SHR. Mechanistically, TDC blocks periostin by regulating TGF-β/Smad signaling pathway in kidney both in vivo and in vitro. Preventing periostin-mediated renal fibrosis and inflammation might be a promising strategy for the treatment of hypertensive renal injury.